De Bowers a Windsor: o longo trajeto constitucional da liberdade ao encontro com a igualdade e a diferença - Maria Fernanda Salcedo Repolês (2016)
In this article it is dealt with one of the most important issues of constitutional thought: the relationship between majority rule and minority rights. In it, it is tried to demonstrate the relevance of the notion of non-discrimination for the acknowledgement of rights of the homosexual community by the Supreme Court of United States of America, in which the constitutional meaning of equality and freedom has, gradually and in midst of disputes, converged to the “right to difference”. Beyond that, it is discussed how the majority of the Supreme Court has tried to decide the cases without resorting to “moralistic” positions that arise, explicitly, from “this or that” world vision, working the cases as questions of law, not as an axiological or ethical preference. Lastly, it is necessary to say that the approach, used in this work, is the historical and comparative perspective (diachronic method), because it opens the possibility of questioning past decisions of the United States Supreme Court, as a conversation between the generations.